Development of a colorimetric and fluorescence dual-mode immunoassay for the precise identification of Alicyclobacillus acidoterrestris in apple juice. (June 2021) - Shi, Yiheng; Sun, Yuhan; Qu, Xiaowei; Zhou, Lei; Wang, Zhouli; Gao, Zhenpeng; Hu, Zhongqiu; Yue, Tianli; Yuan, Yahong
Abstract: Alicyclobacillus acidoterrestris is the main hazardous factor leading to deterioration of commercialized fruit juices, as it can result in serious economic loss to the industry. Currently detection methods require high-end equipment with low specificity and sensitivity. To address these problems, we describe herein a monoclonal antibody with high specificity to A. acidoterrestris using a cell wall protein as antigen. A colorimetric and fluorescence dual-mode immunoassay system employing the prepared antibody was then developed based on the quenching effect of oxidized p -phenylenediamine on fluorescein. This approach could accurately differentiate between the target of interest and other bacteria species with enhanced limit of detection of 4.8 × 10 2  CFU/mL. Apple juice artificially contaminated with A. acidoterrestris at the concentration of 1 CFU/mL could be determined as positive after 24 h enrichment. The resulting immunoassay platform provided a rapid, convenient, sensitive, and selective way for detecting A. acidoterrestris, holding great potential as a robust tool for preventing spoilage in the fruit juice industry. Graphical abstract: Image 1 Highlights: A cell-wall-exposed protein of A. acidoterrestris was obtained and used as the antigen. A monoclonal antibody only specific for A. acidoterrestris was prepared. A colorimetric and fluorescence dual-mode immunoassay was proposed for detecting A. acidoterrestris. This method are precisely and sensitively with LOD of 4.8 × 10 2  CFU/mL.